Role of triple test score in the evaluation of palpable breast lump - Smita Sushil Kachewar; Suryakant Dattatraya Dongre (Indian Journal of Medical and Paediatric Oncology)
Introduction: Fine-needle aspiration cytology (FNAC) method is safe, reliable and time saving outdoor procedure with little discomfort to the patient for detecting Carcinoma breast. The efficacy can further be enhanced when physical breast examination, mammography and FNAC (the triple test [TT]) are jointly taken into consideration. Aims and Objectives : The aim was to evaluate the role of TT score (TTS) in palpable breast masses. Materials and Methods: This prospective study was carried out from May 2010 to April 2012. In the subjects referred to the Department of Pathology for FNAC of the breast mass, the TTS was calculated, and histopathological findings were noted. Results: In the study period TTS score was calculated in 200 cases out of 225 FNAC′s of breast. Of 124 benign cases on cytology, only three showed discordant TTS. Out of 62 malignant cases, 61 showed concordant TTS and one case of mastitis on histopathology showed TTS of five. Out of all the benign lesions, two cases of fibrocystic disease and a single case of phylloides tumor gave a TTS ≥6. These cases were diagnosed as infiltrating ductal carcinoma and angiosarcoma respectively on histopathology. Histopathological correlation was possible in only 70 patients. Of these 70, 28 were from the benign category and 42 were from the malignant category. TTS of ≥6 has a sensitivity of 97.44%, specificity of 100%. FNAC has a sensitivity of 88.37%, specificity of 96.42%. Conclusions: TT reliably guides evaluation of palpable breast masses. Histological correlation indicated TTS to be better diagnostic tool than FNAC alone.